Implementasi Kebijakan Kawasan Tanpa Rokok (KTR) Di Kantor Dinas Pendidikan Dan Kebudayaan (P&K) Kota Sukabumi - Sidiq, Maulana; Amirulloh, Muhammad Rijal; Mulyadi, Andi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
In an effort to limit smoking activities among employees, the Office of Education and Culture (P&K) of Sukabumi City implements Regional Regulation No. 3 of 2014 concerning Smoke-Free Areas. This study aims to determine how the implementation of the Smoke-Free Area (KTR) policy is carried out in the Office of Education and Culture (P&K) of Sukabumi City and the obstacles faced by the Office in implementing the KTR policy. This research uses a descriptive qualitative method and employs the theory of Diana M. DiNitto with four dimensions: communication, resources, bureaucracy, and attitudes. Data for this study were obtained from interviews and documentation. The results of the study indicate that the implementation of the Smoke-Free Area (KTR) policy in the Office of Education and Culture (P&K) of Sukabumi City is still not optimal due to inadequate resources, unstructured bureaucracy, and attitudes that show some employees still smoke inside the office. The conclusion of this study is that the implementation of the Smoke-Free Area policy cannot proceed effectively due to several inhibiting aspects, namely communication, resources, bureaucracy, and attitudes. The recommendations provided include the need for more intensive and continuous socialization and education regarding the KTR policy, the enforcement of strict laws with clear sanctions for violators, the provision of supporting facilities such as separate smoking areas, and effective supervision by forming a special monitoring team responsible for ensuring compliance with the KTR policy.